2017
DOI: 10.1186/s13568-017-0493-z
|View full text |Cite
|
Sign up to set email alerts
|

Production of bioactive liver-targeting interferon Mu-IFN-CSP by soluble prokaryotic expression

Abstract: A novel liver-targeting interferon (IFN-CSP) was successfully over-expressed in our previous work. The in vitro and in vivo investigation revealed that IFN-CSP has significant anti-hepatitis B virus (HBV) effect and liver-targeting capacity. However, due to the IFN-CSP tends to form inclusion bodies in recombinant Escherichia coli (E. coli), efficient production of the soluble liver-targeting interferon is a challenge. In view of biomedical application, novel strategies for efficiently expressing liver-targeti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“… 28 , 29 Previous studies have revealed that HTPP can precisely bind to the HSPG to acquire liver-targeting properties and penetrate the cell membrane. 30 , 31 Therefore, we speculated that it might also be targeted to GPC3, and could penetrate tumors.…”
Section: Introductionmentioning
confidence: 99%
“… 28 , 29 Previous studies have revealed that HTPP can precisely bind to the HSPG to acquire liver-targeting properties and penetrate the cell membrane. 30 , 31 Therefore, we speculated that it might also be targeted to GPC3, and could penetrate tumors.…”
Section: Introductionmentioning
confidence: 99%